2004
DOI: 10.1038/sj.onc.1208222
|View full text |Cite
|
Sign up to set email alerts
|

p12CDK2-AP1 mediates DNA damage responses induced by cisplatin

Abstract: We examined the biological role of p12 in cisplatin-mediated responses by using murine ES p12 CDK2-AP1 knockout clones generated by a targeted disruption of murine p12 . Homozygous knockout clones showed an increased cellular proliferation along with an increase in S and a decrease in G2/M phase populations. Interestingly, ES p12 CDK2-AP1 knockout clones showed a resistance to cisplatin treatment along with an increased DNA repair activity assessed by host cell reactivation assay using a cisplatin-damaged re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
22
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 55 publications
4
22
0
1
Order By: Relevance
“…The present study focused on testing the hypothesis that the putative tumor suppressor and cell cycle regulator p12 could also act as an inhibitor of tumor cell growth in vivo. p12 has been shown to induce cell cycle arrest, growth suppression, repression of DNA replication, and apoptosis in vitro (18,20,38,39), and also to regulate cell growth by association with CDK2, DNA polymerase a/primase, and p14 DOC1R (15,16,40). The present study supports previous in vitro observations and suggests that delivery of a p12 murine gene suppresses tumor cell growth in vivo, with specific increases in TUNEL labeling and apoptotic indices and decreases in Ki-67 cell proliferation labeling indices as compared with controls, resulting in an antitumor effect in a manner that is consistent with a role as a tumor growth suppressor in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study focused on testing the hypothesis that the putative tumor suppressor and cell cycle regulator p12 could also act as an inhibitor of tumor cell growth in vivo. p12 has been shown to induce cell cycle arrest, growth suppression, repression of DNA replication, and apoptosis in vitro (18,20,38,39), and also to regulate cell growth by association with CDK2, DNA polymerase a/primase, and p14 DOC1R (15,16,40). The present study supports previous in vitro observations and suggests that delivery of a p12 murine gene suppresses tumor cell growth in vivo, with specific increases in TUNEL labeling and apoptotic indices and decreases in Ki-67 cell proliferation labeling indices as compared with controls, resulting in an antitumor effect in a manner that is consistent with a role as a tumor growth suppressor in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Also, cell proliferation (proliferating cell nuclear antigen labeling index) was found to increase progressively through hamster oral malignant progression, whereas p12 expression levels progressively decreased through malignant progression (19). Finally, recent data using murine p12-targeted ES knockout clones (p12À/À) showed that in the absence of p12 expression, cellular proliferation is increased, with an increase in S phase and a decrease in G 2 -M phase populations, and apoptosis is significantly reduced with cisplatin treatment (20). In combination, these in vitro data support the role of p12 in regulating tumor cell phenotype and growth; however, specific examination of p12 antitumor effects had not been evaluated previously in vivo.…”
mentioning
confidence: 99%
“…Ϫ/Ϫ mESCsHeterozygous and homozygous Cdk2ap1 knock-out mESCs were generated as reported previously (13). We found the homozygous knock-out of Cdk2ap1 in mice resulted in the embryonic lethality at embryonic days 3.5-5.5 (22).…”
Section: Altered Differentiation Competency In Cdk2ap1mentioning
confidence: 99%
“…CDK2AP1 has been shown to be an S-phase regulator through two important cellular partners: CDK2 and DNA polymerase-␣/primase (14,15). Murine embryonic stem cells with disrupted expression of Cdk2ap1 showed an increased proliferation and an altered cell cycle profile with a reduced G 2 /M phase along with an increased CDK2 activity (13). Recently, Cdk2ap1 has been identified as one of the stem cell-specific genes that are enriched in both embryonic and adult stem cells (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation